The Effect of Epidural Steroids on Postoperative Pain and Hospital Stay in Patients Having a Single-Level Lumbar Discectomy - Naseer Hassan; Raza Hassan; Muhammad Usman; Farooq Azam; Hanif Ur Rehman; Alamzeb Jadoon; Momina Saleem (Gandhara University, 2023)
OBJECTIVES To determine the effect of Epidural steroids on postoperative pain and hospital stay in patients having a single-level lumbar discectomy. METHODOLOGY A quasi-experimental study was conducted at the Neurosurgery department, Qazi Hussain Ahmad Medical Complex, Nowshera.  Sixty patients with a mean age of 40.3±9.21 years were enrolled. The enrolled patients were divided into two groups: Group A patients were given intraoperative epidural methylprednisolone 80 mg, while Group B patients were given only normal saline. Pre- and post-operative pain was assessed after 6 hours, 12 hours and at the discharge time from the hospital. The duration of hospital stay was also noted. RESULTS Out of 60 patients, 55.0% were male, and 45.0% were female, with an overall mean age of 40.3±9.21 years. The VAS score in Group A was 0.82±0.26 compared to 2.30±0.71 in group B (P <0.000). And at first follow-up, the VAS score was 0.13±0.05 and 1.25±0.33 in groups A and B, respectively.   The length of hospital stay was 1.39±0.44 and 1.98±2.50 in groups A and B, respectively. CONCLUSION Intra-operative epidural steroid is beneficial in reducing post-operative pain and hospital stay.